Marketing Communication Strategies of Tourism in @Oasis Sukabumi Increasing Tourist Visits - Hilda Sri Rahayu; Zeffanya Raphael Wijaya (Cakrawala Repositori IMWI, 2024)
Marketing communication strategy is one of the factors that greatly influences the number of visitors at a tourist attraction because it is a design for how to influence the public in various ways so that people know, are then interested in visiting and even revisiting for tourists who have already visited. This research aims to find out and find the formulation of an oasis tourism marketing strategy in Sukabumi Regency. The research method uses case studies. The results of the research show that the marketing and public relations division of Oasis Nature Tourism in conducting tourism marketing uses integrated tourism marketing communications (marketing communication mix), but several aspects such as promotion, human resources, development of small and medium business units and media relations are still weak, so they need to be strengthened. and further guidance accompanied by evaluation and monitoring regarding these aspects. One thing that needs to be developed in the long term is to try to form the branding of tourist destinations to further increase the attractiveness of tourist visits.